2016
DOI: 10.1007/s00261-016-0763-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications for imaging of vascular invasion in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the second largest cause of cancer mortality in the world, with vascular invasion being one of the most important prognostic factors. HCC with tumor thrombus was traditionally considered to have very limited treatment options. However, multiple promising treatment strategies have emerged in recent years, with diagnostic and interventional radiologists playing a major role in patient management. We provide a comprehensive update on the diagnosis and management of HCC with vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 67 publications
0
2
1
Order By: Relevance
“…Thus, for such patients, tumor size should not be a limiting factor for LT. Preoperative examinations such as computed tomography (CT) scans or magnetic resonance imaging (MRI) could only identify macrovascular involvement, while microvascular invasion is conventionally confirmed by postoperative pathological examination. Nowadays, though technically immature, several advanced methods have been developed to predict vascular invasion in HCC patients . The further maturity of relevant technologies could possibly bring breakthroughs to clinical practice.…”
Section: Discussioncontrasting
confidence: 65%
“…Thus, for such patients, tumor size should not be a limiting factor for LT. Preoperative examinations such as computed tomography (CT) scans or magnetic resonance imaging (MRI) could only identify macrovascular involvement, while microvascular invasion is conventionally confirmed by postoperative pathological examination. Nowadays, though technically immature, several advanced methods have been developed to predict vascular invasion in HCC patients . The further maturity of relevant technologies could possibly bring breakthroughs to clinical practice.…”
Section: Discussioncontrasting
confidence: 65%
“…The transmission and dissemination route require passage through the portal venous system and are intimately associated with the tendency towards venous invasion (25). v) Baheti et al (26) reported that the invasion rate of liver cancer was greater in the hepatic portal veins than in the intrahepatic veins, and greater in the intrahepatic veins than in the hepatic arteries. They also suggested that liver cancer is mainly supplied by blood from the hepatic arteries, with the hepatic portal veins supplying only a small percentage of the blood.…”
Section: Discussionmentioning
confidence: 99%
“…These advancements in imaging for MVI diagnosis have allowed for the transition from relying on subjective qualitative radiologic features to the more accurate quantitative radiomics analysis. This has been achieved via the modeling of simple sequences or techniques and the combination of multiple indexes and different techniques with clinical biomarkers, which has greatly improved the diagnostic efficiency of MVI ( 10 - 12 ). However, although the studies in this field have achieved excellent results, there is still no consistent imaging criteria for MVI diagnosis, which greatly impedes its clinical application.…”
Section: Introductionmentioning
confidence: 99%